2020
DOI: 10.20396/bjos.v19i0.8658782
|View full text |Cite
|
Sign up to set email alerts
|

Attractive perception of profile class II patients treated with extractions versus dentoalveolar mandibular advancement devices

Abstract: Aim: This study aimed to compare the esthetic perceptionof profile silhouette of pictures of class II patients before andafter treatment (extractions or mandibular advancement),according to a visual analog scale (VAS) among orthodontists,general dentists and lay people. Methods: A presentation of 18class II adult patients silhouette was shown to three groups ofparticipants (25 orthodontists, 25 general dentists, and 25 laypeople) in two phases in an cross-sectional survey study. An initialpresentation pre-trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
(18 reference statements)
0
2
0
Order By: Relevance
“…Facial asymmetry refers to an incomplete match in size, location, and shape of bilateral structures in relation to the centerline [ 24 ]. As most people have this asymmetry, it has been referred to as one of the morphological characteristics of the body [ 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Facial asymmetry refers to an incomplete match in size, location, and shape of bilateral structures in relation to the centerline [ 24 ]. As most people have this asymmetry, it has been referred to as one of the morphological characteristics of the body [ 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Yogosawa suggested that skeletal abnormalities can be covered by soft tissues, such as muscles and skin [ 30 ]. Duran et al [ 31 ] and Shamlan and Aldrees [ 24 , 32 ] reported that people with symmetrical facial features still have skeletal asymmetry and proved that there is a difference in the degree of asymmetry between hard and soft tissues. Ferrario et al [ 33 ] and Haraguchi et al [ 34 ] identified differences between the hard and soft tissues in terms of the role of asymmetry in recognizing class III asymmetry of the craniofacial skeleton.…”
Section: Introductionmentioning
confidence: 99%